PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOMETHINC - Yasmin, Diva; Pratomo, Triaji (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Currently, Indonesia has many cosmetic and skin care brands that are popular with teenagers and adult women, one of which is the Somethinc brand. Somethinc product is one of the local serum champions in Indonesia who can grasp the beauty and skin care needs of women and men with diverse skin conditions for consumers. Increasing in the cosmetics and skin care sector is due to encouragement from influential people such as influencers on social media who often make evaluations about cosmetic or skin care goods and display how they utilize their products to their followers. This research was undertaken to assess the effect of pricing and promotion on purchasing decisions for Somethinc goods.The sort of research used is descriptive research employing quantitative research methods. The sampling approach is non-probability sampling technique with 100 respondents. The data analysis technique uses descriptive analysis and multiple linear regression.The results of this descriptive study reveal that prices, promotions, and purchase decisions are included in the positive category. The results of multiple linear regressions suggest that the effect of price and promotion on purchase decisions has a coefficient of determination of 85.4% influencing purchasing decisions, the remaining 14.6% is influenced by other independent factors not explored in this study.